Ethnography in foreign language teaching (2004)
The aim of the present article is to describe ethnography as a qualitative approach frequently applied in foreign language acquisition research (Pollard,1985; Smith, 1992; Robinson-Stuart and Nocon, 1996). Reviews of two studies having used ethnographic techniques are presented in the paper to highlight the theoretical background for such an investigative method. The first study discusses issues about participant observation, while the second depicts the language learner in the role of the ethnographer. The paper also tries to throw light on the various tasks of the ethnographer as well as the values (emic and holistic view) and limitations (the insider/outsider dilemma) of ethnography. Key words: Culture, Ethnography, Ethnographer, Qualitative Research- Techniques, Participant Observation El objetivo de este artículo es describir la etnografía como un método cualitativo que es utilizado frecuentemente en la investigación de la adquisición de una lengua extranjera (Pollard, 1985; Smith, 1992; Robinson-Stuart and Nocon, 1996). En el documento se presentan reseñas de dos estudios que implementaron técnicas etnográficas, con el propósito de resaltar los antecedentes históricos de este tipo de método de investigación. El primer estudio trata acerca de temas relacionados con la observación de los participantes, mientras que el segundo estudio presenta al aprendiz de lengua en el rol de etnógrafo. El documento también da varias pautas sobre las tareas del etnógrafo, así como los valores (el punto de vista émico y holístico) y las limitaciones (el dilema interno y externo) de la etnografía. Palabras claves: Cultura, Etnografía, Etnógrafo, Técnicas InvestigaciónCualitativa, Observación Participativa